Education On The Management Of Covid-19 Symptom Complaints As An Effort To Increase Work Productivity: A Community Empowerment - Febri Endra Budi Setyawan; Feny Tunjungsari (Universitas Muhammadiyah Malang, 2022)
In December 2019 an infection by a virus was discovered, finally declared by WHO as a Covid-19 pandemic. The first case in Indonesia was first identified in March 2020. Clinical complaints of COVID-19 patients are quite broad, ranging from asymptomatic, mild symptoms, pneumonia, severe pneumonia, ARDS, sepsis, to septic shock. The most common symptoms are fever, fatigue or myalgia, and dry cough. To be able to understand the symptoms of Covid-19, it is necessary to have sufficient knowledge to be able to take an attitude in dealing with the symptoms that arise. Efforts to increase knowledge and attitudes can be done through education. Purpose: The implementation of this education is expected to increase knowledge and attitudes towards the management of Covid-19 symptoms in employees. Methods:Education was conducted on 192 company “X” employees who were selected by simple random sampling. Service activities were carried out in April 2021 using an instrument in the form of a questionnaire. Results: In the analysis of the results, it is known that educational activities about the management of Covid-19 symptoms influence the knowledge and attitudes of employees about the management of Covid-19 symptoms. Productive aged 30-50 years have a good response to the increase in knowledge and attitudes. It also provides an increase in employee productivity. Conclusion:Good knowledge and a positive attitude have an impact on the comfort of the work environment so that it can make employees feel comfortable at work and improve productivity.